Scaffold curvature-mediated novel biomineralization process originates a continuous soft tissue-to-bone interface. (15th September 2017) - Paris, Michael; Götz, Andreas; Hettrich, Inga; Bidan, Cécile M.; Dunlop, John W.C.; Razi, Hajar; Zizak, Ivo; Hutmacher, Dietmar W.; Fratzl, Peter; Duda, Georg N.; Wagermaier, Wolfgang; Cipitria, Amaia
Graphical abstract: Abstract: A myriad of shapes are found in biological tissues, often naturally evolved to fulfill a particular function. In the field of tissue engineering, substrate geometry influences cell behavior and tissue formation in vitro, yet little is known how this translates to an in vivo scenario. Here we investigate scaffold curvature-induced tissue growth, without additional growth factors or cells, in an ovine animal model. We show that soft tissue formation follows a curvature-driven tissue growth model. The highly organized endogenous soft matrix, potentially under mechanical strain, leads to a non-standard form of biomineralization, whereby the pre-existing organic matrix is mineralized without collagen remodeling and without an intermediate cartilage ossification phase. Micro- and nanoscale characterization of the tissue microstructure using histology, backscattered electron (BSE) and second-harmonic generation (SHG) imaging and synchrotron small angle X-ray scattering (SAXS) revealed (i) continuous collagen fibers across the soft-hard tissue interface on the tip of mineralized cones, and (ii) bone remodeling by basic multicellular units (BMUs) in regions adjacent to the native cortical bone. Thus, features of soft tissue-to-bone interface resembling the insertion sites of ligaments and tendons into bone were created, using a scaffold that did not mimic the structural or biological gradients across such a complex interface at its mature state. This study provides fundamental knowledge for biomimetic scaffold design in the fields of bone regeneration and soft tissue-to-bone interface tissue engineering. Statement of significance: Geometry influences cell behavior and tissue formation in vitro. However, little is known how this translates to an in vivo scenario. Here we investigate the influence of scaffold mean surface curvature on in vivo tissue growth using an ovine animal model. Based on a multiscale tissue microstructure characterization, we show a seamless integration of soft tissue into newly formed bone, resembling the insertion sites of ligaments and tendons into bone. This interface was created using a scaffold without additional growth factors or cells that did not recapitulate the structural or biological gradients across such a complex tissue interface at its mature state. These findings have important implications for biomimetic scaffold design for bone regeneration and soft tissue-to-bone interface tissue engineering.